Randomised controlled trial evaluating the short-term analgesic effect of topical diclofenac on chronic Achilles tendon pain: a pilot study. Issue 4 (4th May 2017) - Bussin, Erin Rebecca; Cairns, Brian; Bovard, Jim; Scott, Alexander
Abstract : Objectives: To determine if a topically applied non-steroidal anti-inflammatory drug (diclofenac) can provide short-term pain relief for chronic Achilles tendinopathy (CAT), in order to inform the development of a new rehabilitation protocol. Design and setting: Pilot double-blind, cross-over randomised controlled trial providing participants with tertiary care. The study was conducted at a single research centre in Vancouver, BC. Participants: Sixteen adults with unilateral CAT and three adults with bilateral CAT participated. Interventions: Participants received two successive treatments (10% diclofenac gel or placebo gel) in random order over a 3-day period. There was a 1-week washout period between the treatments. Allocation was by simple randomisation, and the participants as well as the assessing/treating researcher were blinded to treatment allocation. Outcome measures: The primary outcome measure was pain level (0–10) during tendon loading (hopping). Secondary outcome measures included pain at rest, pressure pain threshold of the Achilles tendon and symptom improvement. Results: Nineteen adults participated in the study, and all were included in the analysis. Diclofenac gel significantly reduced the average pain during tendon loading (p<0.001) and at rest (p=0.031). The average baseline hopping pain was 4.8/10 (95% CI 3.92 to 5.68) and was reduced to 3.1/10 (2.35–3.85) by diclofenac. Pain at rest was decreased and pressure pain threshold increased with diclofenac treatment, but not with placebo gel. There were no observed or reported side effects of either treatment. Conclusions: In this small, short-term study, diclofenac was able to improve symptoms and reduce pain during tendon loading in participants with CAT, whereas placebo gel was not. A future study of diclofenac as a supplement to rehabilitation, with longer follow-up and powered to detect a difference between diclofenac and placebo, is indicated. Trial registration: ISRCTN60151284, http://www.isrctn.com/ISRCTN60151284 Ethics: UBC Clinical Research Ethics Board approval was obtained for this research. The certificate number of the ethics certificate of approval to conduct research is H15-00999.